2022
DOI: 10.1145/3555583
|View full text |Cite
|
Sign up to set email alerts
|

"I've talked without intending to": Self-disclosure and Reciprocity via Embodied Avatar

Abstract: Considering the importance of self-disclosure in building relationships, it is vital to investigate how self-disclosure is affected via avatars in virtual environments, as they are likely to become increasingly popular. Previous work has shown that using avatars increases friendliness and honesty. However, issues such as how and what types of avatars affect self-disclosure and reciprocity have not been fully explored. We conducted a study with 108 participants (54 dyads) discussing a personal topic using one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Although the past study showed that self-disclosure occurred when people started establishing trust with each other (Maloney et al, 2020), it can be challenging when building trust and rapport in a cueless environment. In the context of video-based communication, various existing approaches have been proposed to enable users to display nonverbal cues using their avatars for supporting relationship building, such as showing gaze (Pan et al, 2014) or changing the appearance or facial expression of one's avatar (Hyde et al, 2015;Ichino et al, 2022). However, in the context of social VR, little has been explored about the effect of avatars' nonverbal behavior on rapport building in group discussions.…”
Section: Open Accessmentioning
confidence: 99%
“…Although the past study showed that self-disclosure occurred when people started establishing trust with each other (Maloney et al, 2020), it can be challenging when building trust and rapport in a cueless environment. In the context of video-based communication, various existing approaches have been proposed to enable users to display nonverbal cues using their avatars for supporting relationship building, such as showing gaze (Pan et al, 2014) or changing the appearance or facial expression of one's avatar (Hyde et al, 2015;Ichino et al, 2022). However, in the context of social VR, little has been explored about the effect of avatars' nonverbal behavior on rapport building in group discussions.…”
Section: Open Accessmentioning
confidence: 99%